Analisis Implementasi Kebijakan Perizinan Praktik Dokter di Kabupaten Bekasi Tahun 2021: Studi Kualitatif - Sholihah, Enny Mar'atus; Ramadhan, Syahrul; Ramadhania, Farhaiza; Pradhana, Andrea Thrisiawan (Universitas Airlangga, 2024)
Background: Based on the Regulation of the Minister of Health of the Republic of Indonesia Number 2052/Menkes/Per/X/2011 concerning License to Practice and Implementation of Medical Practice states that doctors and dentists who already have a License to Practice (SIP) and provide medical services or provide expertise consultation in the event requested by a health service facility. However, there is a problem that some practices do not have a SIP. Objectives: This study aims to evaluate the license policy of doctors to practice in Bekasi using the van meter van horn approach Methods: This qualitative research is descriptive evaluative with a case study research design. The research location is in Bekasi Regency. Policy evaluation uses van meter van horn approach by identifying several aspects, namely performance indicators, human resources, clarity of purpose, accuracy and consistency of communication, bureaucratic structure, understanding of policies and responses to policies, social influences, political influences and economic influences on the implementation of medical practice licenses in Bekasi Regency. Results: Results obtained by 12 informants from different agencies. Performance indicators show that licensing carried out by the Investment and One-Stop Integrated Services Agency (DPMPTSP) takes a long time. In terms of human resources, almost all informants stated that there was a difference between HR needs between before and during Covid. Communication indicators show that there are obstacles in the form of double communication. Policy indicators obtained results that have been carried out well and there is no policy rejection given by the government. Meanwhile, it was found that there was no social, economic and political influence with the implementation of the current policy. Conclusion: The performance indicators of the Hospital doctor's license are clear, the performance achievement of the doctor's practice license policy is good, but in the implementation of the doctor's practice license, the obstacle faced is the lack of implementing human resources.